Principal Leadership in Strengthening Students’ Qur’anic Worship Habits through the KAIH Program - Estiyowati Estiyowati; Agus Tinus; Kuncahyono Kuncahyono (MASI Mandiri Edukasi, 2026)
Cultivating religious character in elementary schools requires systematic leadership to transform national habituation programs into sustainable practices embedded within school culture and organizational routines. The Seven Habits of Great Indonesian Children (KAIH) movement was introduced to strengthen students’ character development; however, the leadership mechanisms that support its implementation remain insufficiently explored. This study aims to examine how principal leadership strengthens the implementation of the KAIH program in improving students’ Qur’anic worship habits at an Islamic elementary school. This research employed a qualitative case study design using semi-structured interviews, observations, and documentation. Participants consisted of one principal, two sixth-grade teachers, two Qur’anic tutors, four parents, and 54 sixth-grade students selected through purposive sampling. Data were analyzed using an interactive qualitative analysis model involving data reduction, data display, and conclusion drawing. The findings reveal that the principal’s leadership is enacted through three interconnected dimensions: managerial leadership that establishes systematic planning, monitoring, and organizational support; exemplary leadership that demonstrates religious values through direct participation in worship activities; and motivational leadership that sustains commitment through training, appreciation, and continuous guidance. These integrated leadership dimensions strengthen students’ worship discipline, awareness, and consistency both at school and at home. Furthermore, this study proposes an integrated leadership mechanism model in which exemplary leadership functions as the foundational element reinforcing managerial and motivational practices to ensure the sustainability of religious habituation programs in Islamic elementary schools.